2021
DOI: 10.1097/scs.0000000000007958
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nasal Function and Upper Airway Morphology After Bi-Maxillary Surgery Using Rhinomanometry and Computed Tomography

Abstract: This study was performed to evaluate changes in nasal airflow, nasal airway resistance, nasal cross-sectional area, pharyngeal horizontal area, nasopharyngeal and oropharyngeal volume following Le Fort I osteotomy (L1) impaction with sagittal split ramus osteotomy (SSRO) in classes II and III. Materials and Methods: The subjects consisted of 35 patients (6 males and 29 females, 70 sides) 17 of which were diagnosed as class II and 18 as class III who underwent L1 and SSRO. Nasal airflow and resistance were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The potential effects of nasal cavity constriction include sinusitis, respiratory distress, and nasal obstruction. In addition to reports on respiratory disorders associated with maxillary-mandibular movement, 2–5 there are some reports concerning the condition of the nasal passage and nasal obstruction after Le Fort I osteotomy 6–17 . We reported that the contact rate between the inferior turbinate and the nasal cavity floor was 67.7% when the elevation exceeded 4.0 mm with maxillary movement 18 .…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…The potential effects of nasal cavity constriction include sinusitis, respiratory distress, and nasal obstruction. In addition to reports on respiratory disorders associated with maxillary-mandibular movement, 2–5 there are some reports concerning the condition of the nasal passage and nasal obstruction after Le Fort I osteotomy 6–17 . We reported that the contact rate between the inferior turbinate and the nasal cavity floor was 67.7% when the elevation exceeded 4.0 mm with maxillary movement 18 .…”
mentioning
confidence: 65%
“…In addition to reports on respiratory disorders associated with maxillarymandibular movement, [2][3][4][5] there are some reports concerning the condition of the nasal passage and nasal obstruction after Le Fort I osteotomy. [6][7][8][9][10][11][12][13][14][15][16][17] We reported that the contact rate between the inferior turbinate and the nasal cavity floor was 67.7% when the elevation exceeded 4.0 mm with maxillary movement. 18 The inferior turbinate may be an obstacle to the superior movement of the maxilla.…”
mentioning
confidence: 99%
“…Movahed et al 24 reported that partial inferior turbinect-omy with simultaneous Le Fort I osteotomy is a safe method for managing nasal airway obstruction related to hypertrophied turbinates with minimal complications. However, Tsutsui et al 21 showed that maxillary impaction and mandibular advancement did not worsen nasal airway function without additional nasal surgery (septoplasty and reduction of the inferior turbinate). In this study, no additional turbinectomy was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Although our previous report showed that 3 coronal images from the ANS to the PNS were used to measure the inferior nasal cavity area, there were no differences between the 3 images. 21 Therefore, a coronal image between the ANS and PNS was used to measure the rate of the inferior nasal cavity area, which could reflect a typical coronal area of the inferior meatus in this study.…”
Section: Discussionmentioning
confidence: 99%